9. The Isolation of Steptococcus sp on horse’s dental caries in Aceh Tengah Regency - Sagasias Ahmad; Erina Erina; M Daud AK; Darmawi Darmawi; Fakhrurrazi Fakhrurrazi; M. Isa (Universitas Syiah Kuala, 2019)
The purpose of this study was to detect the existence of the Streptococcus sp bacteria in the horses’ dental caries in Aceh Tengah Regency. The caries samples used in this study were taken from 8 horses in Aceh Tengah Regency. The samples were collected using swab on the teeth and then put into Nutrient Broth (NB) media and further were cultured on selective media TSY20B. The bacteria identification was conducted by observing the bacteria’s morphology, Gram staining and biochemical test. The eight samples of the horses’ dental caries showed that Streptococcus sp bacteria could be isolated from all of the collected samples. From this research it could be concluded that Streptococcus sp bacteria was found in the horses’ dental caries and it was one of the causes of the dental caries.